Effectiveness of silt pit as a soil, water and nutrient conservation method in non-terraced oil palm plantations - Bohluli, Mohsen (2014)
Oil palm plantation activities have expanded to include marginal lands such as steep land areas. The problems of steep lands are soil erosion, loss of fertilizers, poor soil water storage and low productivity. In Malaysia, optimum yield production can be achieved by a combination of land area expansion and yield intensification. Silt pit is one of the best management ways to increase oil palm production in steep lands through soil, water and nutrient conservation. The main objective of this study was to evaluate the effectiveness of various dimensions of silt pit to conserve soil, water and nutrients in a non-terraced oil palm plantation. The effectiveness of silt pit as a soil, water and nutrient conservation method was also compared against control which had no conservation practices. Two field experiments were set up in oil palm sites at Tuan Mee in Sg.Buloh, Selangor and Felda Tekam in Pahang. Each field experimental design had five treatments with three blocks (replications). The treatments were control (no silt pit) and four silt pit sizes with different volume and opening areas including: H1 (1×3×1 m), H2 (1.5×3×1 m), H3 (2×3×1 m) and H4 (2×3×0.5 m). Soil samples were taken once every two months for a year at each site. Each sampling set included the soil outside, sediments and below the sediment inside the silt pit. The soil samples were analyzed for soil chemical and physical properties which were: soil pH, cation exchange capacity, Ca, Mg, K, N, P and total C. Soil physical analysis included bulk density, aggregate stability, dry aggregation and soil water retention. Soil water content was measured daily up to 0.90 m from soil surface. Analysis of variance (ANOVA) was used with split-split block experimental design. In Tuan Mee H1 conserved more soil water content in oil palm active root zone compared with other treatments. This is because pits with smaller opening area had bigger W:F ratio which caused higher lateral water infiltration through silt pit’s walls than water percolation through silt pit’s floor area. Among the silt pits, the narrowest pit showed the best effect to improve soil chemical parameters inside and outside of the pit in Tuan Mee. This is because the silt pit with narrower opening area helped the water head to be higher than other wider pits and redistributed dissolved nutrients in top soil. Nonetheless, the same amount of trapped nutrients inside the pit would be leached over a smaller floor area. Hence, the nutrients are concentrated over a smaller soil area in narrow silt pit compared with other treatments. In Tuan Mee silt pits were not able to affect soil physical characteristics. That was because soil physical parameters change slower than soil chemical characteristics and it will take more time to see significant changes on soil physical properties. Silt pits were not effective in terms of soil water content, soil chemical and physical properties improvement in Tekam because there were no run-off and sediments to be trapped in silt pits as sources of redistributed water and nutrients into the soil.